Use of projects methods in study of second context line of computer science - Азизова, Айгюн (Pedagogy and Psychology, 2021)
The relevance of the topic is justified by the many existing interpretations of the cognitive interest of students. The authors note the lack of scientific and methodological research on the problem of the development of the cognitive abilities in the study of computer science and propose to focus on only one aspect of the research. The aim of the study is to develop the content and procedural components of the educational process using the project method to develop the cognitive interest of students in teaching the omputer science. Research objectives: determination of the psychological and pedagogical foundations of the project method for the development of students' cognitive interests in teaching and studying computer science; development of a structural and functional model of the project; development of a methodology for organizing project activities of students in teaching computer science. The article presents the results of the experiment, which testify to the successful use of the project method in teaching informatics.